Tetrahedral sulfur-based dianions stable in the gas phase: Application of the Cederbaum-Dreuw design principles - YUMAK YAHŞİ, AYŞE (AMER CHEMICAL SOC, 2005)
Cederbaum and Dreuw [Chem. Rev. 2002, 102, 181-200] developed an extensive set of examples of small dianions generally stable to autoionization and in some cases to dissociation as well. Their design principles include arranging alternating positive and negative charges in roughly spherical shells, as in the alkaline earth tetrahalides MX42-. This principle embraces a series of surprising tetrahedral oxygen-centered dianions Of O(C-2)(4), O(BN)(4), and O(BeO)(4). These systems are stable with respect to autoionization (their vertical ionization energy is positive) but are metastable with respect to dissociation into monoanions. We present a family of dianions with sulfur cores which are stable both with respect to autoionization and dissociation. The shell charge alternation still contributes to stability, but these systems have a positive core in contrast to the oxo systems' negative core.
Keywords: ELECTRON PROPAGATOR CALCULATIONS; DOUBLY-CHARGED ANIONS; NEGATIVE-IONS; CLUSTER DIANIONS; STABILITY; EXISTENCE; SO4(2-)